Cover Feature: Total Synthesis of a Partial Structure from Arabinogalactan and Its Application for Allergy Prevention (Chem. Eur. J. 3/2021). Issue 3 (27th October 2020) - Krumb, Matthias; Jäger, Maximilian; Voss, Alice; Immig, Loreen; Peters, Karin; Kowalczyk, Danuta; Bufe, Albrecht; Opatz, Till; Holst, Otto; Vogel, Christian; Peters, Marcus
Abstract : Growing up in an alpine farming environment with frequent contact to cowsheds is protective against allergic diseases. Arabinogalactan from this environment is one of the protective compounds. The source of this polysaccharide was traced back to grasses such as Alopecurus pratensis . This study shows that the total synthesis of arabinose and galactose containing partial structures from such arabinogalactan is possible. After coupling of these pentasaccharides to a carrier protein, the glycoconjugates protect against allergic response in a mouse model asthma. More information can be found in the Communication by T. Opatz, M. Peters, et al. on page 928 .